PENDIDIKAN AGAMA DALAM PENTAS WAYANG SANTRI KI ENTHUS SUSMONO - Muhammad Nashrullah; Hamdan Adib (Oasis : Jurnal Ilmiah Kajian Islam, 2021)
Edgar Dale provides a valuable contribution to science, linking media and learning experiences. By adapting Jerome S Bruner's theory which divides experience into three namely active, pictorial and symbolic, and provides the basis use of theory, from the most abstract things to the most concrete things and is formulated in the cone of Edgar Dale's experience theory. This study aims to analyze the wayang santri performances performed by Ki Enthus Susmono using the theory ofEdgar Dale and Jermoe s Bruner. This research is a type of library research research and the data analysis used is content analysis. Ki Enthus Susmono with his wayang wayang santri intended to provide public education about Islamic teachings. The result showed that media used by Ki Enthus in accordance with Edgar Dale’s theory and categorized as both visual and pictoral on Bruner's theory. Learning uses media in the form of images or other visual forms help people understand Islamic teachings brought by Ki Enthus.